2002
DOI: 10.1182/blood.v99.6.2070
|View full text |Cite
|
Sign up to set email alerts
|

Shear-dependent morphology of von Willebrand factor bound to immobilized collagen

Abstract: We have developed an immunogold von Willebrand factor (VWF) detection method that permits almost complete coverage of individual VWF molecules, and by this unequivocal localization and morphologic analysis of collagen-bound VWF by atomic force microscopy (AFM). Perfusion of gel filtration-purified VWF in parallel plate perfusion chambers over glass coverslips coated with calf skin collagen, followed by AFM imaging in air, enabled us to assess possible morphologic differences between VWF bound at low (0.07 N/m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 22 publications
3
29
1
Order By: Relevance
“…In support of the proposition that shear causes large scale changes in protein conformation, surfaceimmobilized VWF has been shown to extend from a globular to an unfolded state upon application of fluid shear (47). Others suggest, however, that this observation may be substrate specific because VWF immobilized on collagen does not undergo similar changes in response to fluid flow (48). In support of the proposition that subtle changes are sufficient for functional alterations, x-ray studies show how point mutations in the A1-domain and GpIb receptor enhance VWF-GpIb binding affinity, without dramatically altering protein structure (19).…”
Section: Discussionmentioning
confidence: 82%
“…In support of the proposition that shear causes large scale changes in protein conformation, surfaceimmobilized VWF has been shown to extend from a globular to an unfolded state upon application of fluid shear (47). Others suggest, however, that this observation may be substrate specific because VWF immobilized on collagen does not undergo similar changes in response to fluid flow (48). In support of the proposition that subtle changes are sufficient for functional alterations, x-ray studies show how point mutations in the A1-domain and GpIb receptor enhance VWF-GpIb binding affinity, without dramatically altering protein structure (19).…”
Section: Discussionmentioning
confidence: 82%
“…Earlier studies demonstrated a shear stress-induced conformational change of VWF from a globular state to an extended chain upon immobilization on an artificial hydrophobic surface [40]. We, in contrast, were not able to show such a large overall shear-induced morphologic shape change on VWF immobilized on collagen but did not exclude small-scale effects of shear on one or more VWF domains [41]. Surface properties itself have an effect on VWF shape [42].…”
Section: Interaction Of Vwf With the Gpib-ix-v Complexmentioning
confidence: 73%
“…Therefore we had to employ AFM imaging of dried samples. Dry AFM imaging has previously been used to study binding of SPARC (Wang et al, 2005) and vWF (Novak et al, 2002) to collagen type I and of laminin to collagen type IV (Chen and Hansma, 2000). The basic morphology of DDR1-Fc dimers and collagen was found to be very similar in fluid vs. dry state based on our previous studies and our current results.…”
Section: Discussionmentioning
confidence: 99%